(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3fSH bjS hdO EdjGS Hf eVQ (B: (3bHS Hf EdjGS f hOgeGf Hf EdjGS hge Cgd HjJ ai bjS hCegeG GdSbjaI HfJ GdZdab Hf GdTGgO s
(3BNQgG (B:s
(3hefge hgH Hf CHj NhjdO Hf Xhjde Hf Yha Hf YbOI (B: (3aGNJUe Hfh ZjQI ai ejQGJg aCYWGg GdfHi Udi Gddg Ydg hSde hgH Hf CejI Hf CHj GdUdJ , hhdO LTe Hf Kbja MWjW Hf LTe , ahdO MWjW LTe hGddg CYde HGdUhGH GfJgi s
(3HgG fXGe GdJYbjHIs
(3fbdkG Yf fSNI eUhQI HOGQ GdcJH GdeUQjI Qbe (B1103 (3JGQjNs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs